FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Tampubolon, David Junior; Susanti, Merry (Jurnal Paradigma Akuntansi, 2025)
This research aims to obtain empirical evidence regarding the effect of leverage, board size, liquidity, and corporate social responsibility on financial performance in manufacturing companies listed in the Indonesia Stock Exchange during the period of 2018-2020. The sample was selected using purposive sampling method and the valid data used in this study found 45 manufacturing companies. The data processing techniques using multiple regression analysis assisted by SPSS software (Statistical Product and Service Solution) version 21. The results of this study showed that leverage has negative and significant effect on financial performance. Meanwhile, board size, liquidity and corporate social responsibility have no significant effect on financial performance. The implication of this study is for the role of the company management to pay attention on the level of leverage used by the company and managed as best as possible so as not to create problems in the future in order to increasing the company’s financial performance.